Timoleague Franciscan Friary, north choir wall, tomb niche, jamb and arch - O'Donovan, Danielle (My University, 2008)
Jamb and arch moulding of tomb niche, from intrados moulding comprises chamfer, quadrant, hollow chamfer, broken quadrant.
Tomb niche
Keywords: quadrant; Architecture, Gothic -- Ireland; Cork (Ireland)--Buildings, structures, etc.; Architecture, Franciscan; Funerary monuments; Late Medieval; roll moldings; moldings, hollow